2011
DOI: 10.2147/oajsm.s17048
|View full text |Cite
|
Sign up to set email alerts
|

Pooled analysis of clinical trial data evaluating the safety and effectiveness of diclofenac epolamine topical patch 1.3% for the treatment of acute ankle sprain

Abstract: This pooled analysis assessed the efficacy and safety of the diclofenac epolamine topical patch 1.3% (DETP) for the treatment of acute mild-to-moderate ankle sprain. Data from 2 randomized, double-blind, placebo-controlled studies enrolling 274 male and female patients aged 18 to 65 years with acute ankle sprain were pooled and evaluated. The primary end point was pain reduction on movement assessed using a 100 mm visual analog scale (VAS). Safety and tolerability were also assessed. Beginning approximately 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Thus, withdrawing the cadet from sport matches for a few term of time seems to be the choice. The excellent results achieved by physiotherapy in cadets receiving conservative treatment of ankle sprains have been described by Lionberger et al [15]. This study con irms the ankle sprain as a common injury in cadets.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Thus, withdrawing the cadet from sport matches for a few term of time seems to be the choice. The excellent results achieved by physiotherapy in cadets receiving conservative treatment of ankle sprains have been described by Lionberger et al [15]. This study con irms the ankle sprain as a common injury in cadets.…”
Section: Resultssupporting
confidence: 76%
“…Many studies on sports injuries have indicated the high incidence of recurrence of ankle sprain [13][14][15][16]; although, investigations on the outcomes of ankle injuries and their in luences on the sports performance level are rare. Ankle sprain is considered to be a very common type of cadets training injury [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with diclofenac sodium and potassium salts, the epolamine salt of diclofenac demonstrates detergent-like properties with improved solubility in both water and organic solvents, facilitating enhanced epidermal penetration [ 47 , 175 ]. Clinical studies in patients experiencing acute pain from minor soft tissue injuries or ankle sprains reported that diclofenac epolamine topical patches provided rapid and effective local analgesia compared with placebo and were generally safe and well tolerated [ 176 178 ]. Diclofenac epolamine (FLECTOR ® IBSA Institut Biochimique SA, Lugano, Switzerland) 1.3 % patches (10 × 14 cm) containing 180 mg of diclofenac were approved by the FDA in 2007.…”
Section: Topical Formulations Of Diclofenac Sodium or Epolamine Salt mentioning
confidence: 99%
“…The safety and efficacy of the marketed DHEP medicated plaster have been demonstrated by data from clinical studies and postmarketing experience of the treatment of acute musculoskeletal pain associated with soft tissue injuries and inflammatory pathologies, including osteoarthritis and A c c e p t e d M a n u s c r i p t other rheumatological conditions 5,8,9,[21][22][23][24][25][26] . Results from a skin permeability and pharmacokinetic study 10 and a pharmacokinetic study in healthy volunteers 27 show that the systemic exposure of diclofenac is very low compared with oral administration when applied as the DHEP medicated plaster.…”
Section: Introductionmentioning
confidence: 99%